Manajemen Kewirausahaan dalam Menumbuhkan Jiwa Entrepreunership di Pondok Pesantren Darun Najah Lumajang - Maghfiroh, Mamluatul; Umam, Khotibul; Abidin, Zainal (MANAGIERE: Journal of Islamic Educational Management, 2024)
Entrepreneurial management is the process of planning, organizing, directing, and controlling resources to create and manage a business. Meanwhile, the entrepreneurial spirit is the ability to create something new and different through creative thinking processes and innovative actions. The focus of this research consists of: 1) What are the forms of entrepreneurial management at the Darun Najah Lumajang Islamic boarding school; 2) What are the results of the entrepreneurship program at the Darun Najah Lumajang Islamic boarding school; and 3) What are the inhibiting and supporting factors in fostering an entrepreneurial spirit at the Darun Najah Lumajang Islamic boarding school. This research uses a qualitative approach, which produces descriptive data with a case study type. Data collection techniques included passive participant observation, semi-structured interviews, and documentation. Data validity uses triangulation and member checks. Data analysis uses data condensation, data presentation, and drawing conclusions. The results of this research are: 1) Forms of entrepreneurial management starting from coordination meetings with foundations, specialization of training programs, division of entrepreneurial fields, 2) The results of entrepreneurship programs provide benefits for students and alumni, as well as the economic independence of Islamic boarding schools. 3) Supporting factors to foster an entrepreneurial spirit: facilities accommodating, coaching, and inhibiting factors such as the lack of awareness of students and busy schedules.